2014
DOI: 10.2298/jsc130818133s
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of aqueous solutions of potassium carbonate + glycine as a solvent for carbon dioxide removal

Abstract: The physical properties, such as densities, viscosities, and refractive indices, of aqueous solutions of potassium carbonate (PC) blended with glycine (Gly) as solvent blends for CO 2 capture were measured. The properties were measured at ten different temperatures from (298.15 to 343.15) K. The mass fractions (w 1 +w 2 ) of the (PC+Gly) blends were 0.05+0.01, 0.10+0.02, 0.15+0.03, 0.20+0.04, 0.25+0.05, 0.30+0.06, 0.35+0.07 and 0.40+0.08 %, respectively. An analysis of the experimental results showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…µ water = 1.86 × 10 −6 exp 16400 RT (21) The liquid viscosity of 15wt.% PC + 3 wt.% GLY can be approximated using the correlation provided by Shuaib et al [15], as shown in Equation 22:…”
Section: Reaction Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…µ water = 1.86 × 10 −6 exp 16400 RT (21) The liquid viscosity of 15wt.% PC + 3 wt.% GLY can be approximated using the correlation provided by Shuaib et al [15], as shown in Equation 22:…”
Section: Reaction Modelmentioning
confidence: 99%
“…The potential of PCGLY is supported by its environmental friendly properties and has less toxicity than MDEA [24,27]. PCGLY also requires lower regeneration energy as compared to MDEA [15,27,32,52]. Due to the high solvent temperature in the absorber, the required energy for stripping process is lower.…”
Section: Pcgly As Potential Green Solventmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 Another reported solubility data 21 has shown that 15 wt % PC + 3 wt % glycine is sufficient for the removal of CO 2 at high pressure, thus encouraging the experimental work to be conducted at a bench scale mini pilot plant. 6 Then, regression of physical properties, particularly the density and viscosity that were obtained from the literature, 22 are carried out in Aspen Plus.…”
Section: Research Methodologymentioning
confidence: 99%
“…CO 2 capture process [12][13][14][15]. Among the studied amino acid salts, L-prolinate is the most promising to be used for CO 2 capture [15,16].…”
Section: Accepted Manuscriptmentioning
confidence: 99%